Exaggeration In Defining The Common Error In University Books Through Kitab Al-Tahrir Al-Kitabi Al-Wadhifi/ المبالغة في تحديد الخطأ الشائع في الكتب الجامعية من خلال كتاب التحري الكتابي الوظيفي والإبداعي - Alamri, Saeed Ali Muhammed (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2024)
Every language has rules, laws, and systems that govern it. Usually, the more advanced generations establish them automatically. Then circumstances immediately change them for the next generation, and something similar to violating these rules and laws occurs, and the pronunciation of words or their meanings change. If the old system is immune, the change is considered modern. This study uses a descriptive and analytical approach by collecting data presented in the book by Dr. Atef Fadl Muhammad, then describing it, analyzing it, and responding to its errors. Some researchers go too far in this regard and consider what they deny about the change as a common mistake, and perhaps they need to catch the fact that this is true in Arabic because it is a direct standard and a dividing line for truth and error. This study proves that much of what researchers imagine (and the book above is an example of researchers' blogs) is not a common mistake but is true, supported by something that eliminates doubt. Whatever is true about the Arabs is accurate, and whatever contradicts their words is false. The words of the Arabs do not have the same level of power, but we do not judge anything that comes from them as false, regardless of the level of control. From this, we have seen many things recorded as common language mistakes, but they are true, and this is what this study is based on. This study monitors the frequency of researchers describing words and methods as common mistakes, discussing them, and whether all that is observed is an honest mistake or a belief contrary to the truth. This study concluded that these are simply beliefs and not facts, as many things recorded as false are aspects of what is true.